The Effect of Patient Safety Culture on the Quality of Nurses’ Performance - Ririk Harlin; Djazuly Chalidyanto; Ririn Indah Permatasari (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
Patient safety culture should be applied by all nurses in healthcare facilities. Yet, most of the time, nurses are not aware of its importance, resulting in patients’ poor perception of the nurses’ performance. This study identified the effect of patient safety culture on nurses’ performance at Bakti Mulia General Hospital. This was a correlation-descriptive study, which selected all nurses as many as 28 at Bakti Mulia General Hospital by using simple random sampling. Data were collected through questionnaires and analyzed using univariate and bivariate analysis with Pearson Correlation test. The majority of the respondents had poor patient safety culture (46%), and some had high patient safety culture (54%). The majority of the respondents showed had poor performance (68%), and some others had high performance (32%). There was a significant effect on patient safety culture on nurses' performance at Bakti Mulia General Hospital.